Perceived social support and family members of patients with mental disorders: A mixed method study - Amini, Shabnam; Jalali, Amir; Jalali, Rostam (Frontiers in Public Health, 2023)
Introduction: Family members are the caregivers to patients with mental disorders at home and the mental and spiritual pressures caused by this responsibility necessitate physical, mental, and perceived social supports for these families. The present mixed method study is an attempt to elaborate on the perceived social support by Iranian families with chronic mental disorder patients. Materials and Methods: Throughout a sequential mixed methods explanatory study (quantitative and qualitative), 200 family members of patients with chronic mental disorder were selected through convenient sampling (quantitative phase). Data gathering was started using a demographics form and Stewart and Sherburne's perceived social support scale. The qualitative phase included 10 participants who obtained low scores in the quantitative phase and took part in private, face to face, in-depth, and semi-structured interviews. The data obtained in the quantitative phase were analyzed using statistical tests and the interviews were analyzed using qualitative content analysis. Findings: The perceived social support by the participants was at moderate level in different fields of tangible support, information and emotional support, kindness, and positive social interactions. The results of qualitative phase revealed social support status in 15 subcategories, six categories, and two themes of support and acceptance by family, relatives, and friends; and support and being understood by society. The results of the qualitative and quantitative sections emphasized on the needs of patients' family members (who acted as caregivers for patients) for support in family, social, and emotional areas. Conclusion: The members of families with chronic mental disorder patients have different needs in the area of perceived social support. Such needs are more tangible in family members like children with mentally ill parents or parents with mentally ill children. The results of this study can be used for educational and supportive planning for caregivers of patients, most of whom are family members.